The practice of classification and the theory of evolution, and what the demise of Charles Darwin's tree of life hypothesis means for both of them - Doolittle, W. Ford (The Royal Society, 2009)
Debates over the status of the tree of life (TOL) often proceed without agreement as to what it is supposed to be: a hierarchical classification scheme, a tracing of genomic and organismal history or a hypothesis about evolutionary processes and the patterns they can generate. I will argue that for Darwin it was a hypothesis, which lateral gene transfer in prokaryotes now shows to be false. I will propose a more general and relaxed evolutionary theory and point out why anti-evolutionists should take no comfort from disproof of the TOL hypothesis.